Does Turkey have a Central Asian Project? - Ali Emre Sucu; O. I. Iskandarov; R. B. Mahmudov; D. N. Chernov (Vestnik MGIMO-Universiteta)
Central Asia's importance in Turkish foreign policy has begun to rise since the beginning of the 2010s. Turkey determines its regional policy in the conception of the Turkic world, including Azerbaijan. With this regard, Turkey pays particular attention to the institutionalization of bilateral relations with the regional states. The most successful measure in that direction is the establishment of the Turkic Council. This integration project marks significant progress for the institutionalization of Turkey's Central Asian policy. Turkey is one of the non-regional actors affecting the Central Asian balance of power. However, it has limited influence on regional security and military affairs, which Russia dominates. Turkey is only a secondary non-regional actor in Central Asia. Therefore, it primarily structures its Central Asian policy using common historical and cultural elements. In this study, we investigate whether Turkey has a long-term project in Central Asia. For this purpose, we explore the restrictions of Turkish policy in Central Asia. After that, we compare Turkey's importance for the foreign policies of Central Asian states. Additionally, we evaluate Turkey's interest in non-Western organizations such as the Eurasian Economic Union and the Shanghai Cooperation Organization to transform Turkish foreign policy priorities in recent years. Finally, we show that Turkey has a policy toward Central Asia but not a fully-fledged project for the region.